The Long-Term Decline Of The "Ummah" Vote: A Seven-Decade Electoral Trajectory Of Islamic Parties In Indonesia (1955–2024) - Suwarko, Andi; Ul Khaq, Muhammad Adwa (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the longitudinal electoral performance of Islamic political parties in Indonesia over seven decades, from the landmark 1955 election to the 2024 polls. Despite Indonesia's significant societal shift toward increased public piety, Islamic parties—including Masyumi, NU, PPP, PKS, PAN, and PKB—have faced a paradoxical stagnation and long-term decline in their aggregate vote share. Using a mixed-methods approach that integrates historical institutionalism with quantitative trend analysis, this research identifies the structural and agency-driven factors behind this "Ummah vote" depletion. The findings reveal that the robust "aliran" (stream) politics of 1955, which once commanded 44% of the vote, has been eroded by persistent fragmentation, the "nationalist appropriation" of religious symbols, and a shift toward clientelistic pragmatism. We argue that Islamic parties face a "survival vs. identity" dilemma: while moderate metamorphosis allows them to remain in governing coalitions, it dilutes their ideological distinctiveness, leading to electoral decay. This study verifies the "Inclusion-Moderation" thesis in the Indonesian context, suggesting that as these parties become embedded in the secular-pragmatic democratic framework, they lose their monopoly over the Muslim electorate. This research contributes to the global discourse on political Islam by demonstrating that social religiosity does not automatically translate into religious party hegemony in a competitive democratic marketplace.